Code for What?: Computer Science for Storytelling and Social Justice - Lee, Clifford; Soep, Elisabeth (Cambridge, Massachusetts : The MIT Press, 2022)
"Challenges the 'Code for All' movement with a framework for critical computational literacy that integrates computer science with journalism, data, art, civic imagination, and social action"
Keywords: Computer science -- Social aspects -- Study and teaching -- United States; Computer programming -- Social aspects -- Study and teaching | -- United States; Computer literacy -- United States; Critical pedagogy -- United States; Interdisciplinary approach in education -- United States; Social justice and education -- United States